The Academic Leader's Balancing Act: Managing Time, Stress, and Transitions - Dr. Walter H. Gmelch (Academic Chairpersons Conference Proceedings, 2018)
Dr. Gmelch will explore the many tradeoffs in academic leadership, personal vs. professional and academic vs. administrative. Attendees will focus on distinguishing between high-payoffs (HIPOS) and low-payoffs (LOPOS) to increase focus and effectiveness, and learn to operate their ‘management molecule.’ Common stressers and how to cope with them will be covered while attendees explore effective strategies for departmental decision-making.
Keywords: Balance Time Management Stress Transitions